Heroic Offerings: The Terracotta Plaques from the Spartan Sanctuary of Agamemnon and Kassandra - Stéphanie Huysecom-Haxhi (Les Carnets de l’ACoSt)
Heroic Offerings: The Terracotta Plaques from the Spartan Sanctuary of Agamemnon and Kassandra by Gina Salapata is reviewed by Stéphanie Husecom-Haxhi.